The Problem of Family Integrity in Endogamous Marriages in the Community of Banyuanyar Village, Kalibaru District, Banyuwangi - Jannah, Lailatu; Busriyanti, Busriyanti; Ishaq, Ishaq (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research is motivated by the practice of endogamous marriage in Banyuanyar Village which causes problems with the fraternal gap between the extended family and the nuclear family. Endogamous marriage is marriage in the same environment. This is endogamous marriage within the scope of the family, there is marriage between cousins descended from the same lineage or who still have a family relationship between the two parties, and in a society which only allows members of the community to intermarry or marry other members of their own group, both from the father's line and Mother. The aim of the research in question is to gain knowledge about the problems that exist in the endogamous marriage community in Lekap Hamlet, Banyuanyar Village, Kalibaru, Banyuwangi, so that they have an impact on family integrity, which also requires knowing the implications of endogamous marriage in building family integrity from a legal sociology perspective. The approach used is an empirical approach and includes a type of field research. The location of the research that the author conducted was in Lekap Hamlet, Banyuanyar Village, Kalibaru District, Banyuwangi. The data collection procedures are by means of observation, interviews and documentation. The data collection technique is observation, interviews and documentation. And data analysis uses descriptive analysis.The results of this research are several factors, namely in terms of arranged marriages, there is no compatibility in the arranged marriage which results in divorce which has an impact on the destruction of the brotherhood or the integrity of the extended family.